1999
DOI: 10.1094/mpmi.1999.12.10.901
|View full text |Cite
|
Sign up to set email alerts
|

CFP, the Putative Cercosporin Transporter of Cercospora kikuchii, Is Required for Wild Type Cercosporin Production, Resistance, and Virulence on Soybean

Abstract: Many species of the fungal genus Cercospora, including the soybean pathogen C. kikuchii, produce the phytotoxic polyketide cercosporin. Cercosporin production is induced by light. Previously, we identified several cDNA clones of mRNA transcripts that exhibited light-enhanced accumulation in C. kikuchii. Targeted disruption of the genomic copy of one of these, now designated CFP (cercosporin facilitator protein), results in a drastic reduction in cercosporin production, greatly reduced virulence of the fungus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(167 citation statements)
references
References 39 publications
8
157
0
2
Order By: Relevance
“…Indeed, in bacteria, the secretion of the antibiotics and other secondary metabolites from the cells is performed by either MFS or ABC transporters, depending on the nature of the secondary metabolite (69) . MFS transporters have been identified in the gene clusters of several fungal secondary metabolites, including cephalosporin (129,130) , cercosporin (142) , and roquefortine C (83) , among others. In these cases, it is very likely that the MFSs are involved in peroxisomal transport of intermediates as occurs with the cephalosporin intermediates described in this article.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Indeed, in bacteria, the secretion of the antibiotics and other secondary metabolites from the cells is performed by either MFS or ABC transporters, depending on the nature of the secondary metabolite (69) . MFS transporters have been identified in the gene clusters of several fungal secondary metabolites, including cephalosporin (129,130) , cercosporin (142) , and roquefortine C (83) , among others. In these cases, it is very likely that the MFSs are involved in peroxisomal transport of intermediates as occurs with the cephalosporin intermediates described in this article.…”
Section: Expert Opinionmentioning
confidence: 99%
“…However, whether cercosporin plays a critical role in gray leaf spot has not been proven conclusively, there is considerable evidence that cercosporin is a broadly conserved, key component of pathogenesis among many Cercospora species. Upchurch et al (1991) reported that a cercosporin non-producing mutant of C. kikuchii, generated by UV mutagenesis, was not able to cause typical necrotic lesions on soybean, and Callahan et al (1999) demonstrated that C. kikuchii requires CFP1, a gene predicted to encode an ABC transporter, for protection against the toxic effects of cercosporin and virulence on soybean. In C. zeae-maydis, Shim and Dunkle (2003) demonstrated that the disruption of CZK3, which is predicted to encode a MAP kinase kinase kinase, caused pleiotropic phenotypes, including the abolishment of cercosporin biosynthesis, conidiation, and pigmentation.…”
Section: Cercospora Zeae-maydis Causes Gray Leaf Spot Of Maizementioning
confidence: 99%
“…While fungal MFS transporters were primarily thought to play a role in secretion of toxins (5,39), some MFS transporters have been shown to protect against fungicides. For example, replacement mutants of Bcmfs1, a MSF gene from B. cinerea, showed increased sensitivity to the natural toxic compounds camptothecin and cercosporin, produced by the plant Camptotheca acuminata and the plant pathogenic fungus Cercospora kikuchii.…”
Section: Efflux Transporters Allow Fungi To Grow In the Presence Of Fmentioning
confidence: 99%